STUDY OF THE MAIN STRENGTH CHARACTERISTICS OF GLUED LAMINATED STRUCTURAL BEAMS MADE FROM SOLID WOOD - Bukhanevych , І.; Maievskyi , В.; Udovytskyi , О.; Manziuk , А.; Kopynets , З. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
The necessity and advantages of utilizing glued laminated timber in contemporary construction are supported by its superior technical and technological properties as a structural material. These include its natural environmental friendliness, adequate strength, cost-effectiveness, and energy efficiency. A notable application is in glued laminated timber beams, which, due to the gluing technology, blend the inherent strength of wood with the benefits of engineered materials. These beams exhibit high rigidity at a low weight, ease of processing and disposal, and a commitment to environmental sustainability. The gluing process allows for the elimination of wood defects and enables the production of elements in various lengths and cross-sections, which ensures their extensive applicability. Glued structural beams made from solid wood are primarily manufactured on automated lines, where maintaining optimal temperature and humidity conditions is crucial for ensuring consistently high quality. Furthermore, precise sorting of the raw materials is essential. To evaluate the strength and reliability of finger joints in glued structural beams from solid wood, comprehensive laboratory tests were conducted. The results from these experimental studies indicate that for class C24, the strength values of the mortise and tenon joint range from 35.65 to 50.19 N/mm², with the corresponding modulus of elasticity falling between 9693 and 11339 kN/mm². These experimental findings confirm the high strength and reliability of both glued beams and finger joints, positioning them as a promising structural material in modern construction that can effectively compete with other building materials. The results obtained are applicable for real production processes and for predicting the physical and mechanical characteristics of structures made from glued structural beams of solid wood.